2019
DOI: 10.21608/ejbo.2019.6671.1262
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of essential oils as antifungal agents against Aspergillus fumigatus KY026061causing allergic bronchopulmonaryaspergillosis (ABPA)

Abstract: A LLERGIC bronchopulmonary aspergillosis (ABPA) and invasive aspergillosis are often found in severely immuno-suppressed patients and are characterized by invasion of conidia of Aspergillus fumigatus into blood vessels which can result in dissemination to other organs. Aspergilloma is a fungal ball that develops in previous cavity lung lesions. Essential oils have been used as antifungal agents. Inhalation of vapors of the essential oils kill invaders attached to the inner respiratory lining and work synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In the present study, the antimicrobial activity of the extracellular siderophore TafC was carried out using inhibition zone diameter and results showed that TafC had antibacterial activity, these results matched with Chowdappa et al (2020) who revealed that the antibacterial activity of siderophores produced by Endophytic fungi was determined by a disc diffusion assay where the results proved that the siderophore exhibited the highest zone of inhibition on plant pathogens. Essential oils have been used as antifungal agents against A. fumigatus (Abd El-Zaher et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the antimicrobial activity of the extracellular siderophore TafC was carried out using inhibition zone diameter and results showed that TafC had antibacterial activity, these results matched with Chowdappa et al (2020) who revealed that the antibacterial activity of siderophores produced by Endophytic fungi was determined by a disc diffusion assay where the results proved that the siderophore exhibited the highest zone of inhibition on plant pathogens. Essential oils have been used as antifungal agents against A. fumigatus (Abd El-Zaher et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that phenolic compounds have the ability to alter cell permeability and disrupt the membrane lipid (6). Furthermore, the regulation and function of cell wall synthesis enzymes may also be affected leading to alternation in microbial cell growth and morphogenesis (37,38).…”
Section: Discussionmentioning
confidence: 99%